Implementation of Islamic Education in Mental Healing of Covid-19 Patients: Case Study in Cirebon City - Ahmad Yani (AL-ISHLAH: Jurnal Pendidikan, 2023)
The medical response to the Covid-19 pandemic has started from square one. Yet the psychological effects of the COVID-19 epidemic should not be overlooked either. So that patients can take responsibility for their own mental health throughout their seclusion. This presentation will discuss how Islamic education is being used to aid in the mental recovery of those with Covid-19. The goal of this study is to aid covid sufferers in their recovery through Islamic literacy. This study is a survey that adopts a descriptive qualitative methodology to arrive at conclusions based on an analysis of respondents' personal narratives. The city of Cirebon served as the location for this study. This study will use a sample of 15 covid-19 survivors, 2 members of the survivors' families, and 1 survivor's neighbour as a resource person. According to the results of this study, there are a number of things that COVID-19 patients may do from the standpoint of Islamic education, and these efforts can be broken down into three categories: the patient's bodily health, their mental and spiritual health, and their social health.